2023
DOI: 10.3390/ijms24054950
|View full text |Cite
|
Sign up to set email alerts
|

BMPER Improves Vascular Remodeling and the Contractile Vascular SMC Phenotype

Abstract: Dedifferentiated vascular smooth muscle cells (vSMCs) play an essential role in neointima formation, and we now aim to investigate the role of the bone morphogenetic protein (BMP) modulator BMPER (BMP endothelial cell precursor-derived regulator) in neointima formation. To assess BMPER expression in arterial restenosis, we used a mouse carotid ligation model with perivascular cuff placement. Overall BMPER expression after vessel injury was increased; however, expression in the tunica media was decreased compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…BMPER, also known as the vertebrate homolog of Drosophila cross-veinless 2, was originally identified in a screening assay for differentially expressed proteins in embryonic endothelial precursor cells (44). BMPER interacts with BMP-2, -4, -6, -7, -9 and BMP receptor Ia/b (45,46), and activates the BMP signaling pathway in a concentration-dependent manner (47). Results of a previous study have revealed that exogenous BMPER at low molar concentrations enhances Smad activation (47).…”
Section: Discussionmentioning
confidence: 99%
“…BMPER, also known as the vertebrate homolog of Drosophila cross-veinless 2, was originally identified in a screening assay for differentially expressed proteins in embryonic endothelial precursor cells (44). BMPER interacts with BMP-2, -4, -6, -7, -9 and BMP receptor Ia/b (45,46), and activates the BMP signaling pathway in a concentration-dependent manner (47). Results of a previous study have revealed that exogenous BMPER at low molar concentrations enhances Smad activation (47).…”
Section: Discussionmentioning
confidence: 99%